The Influence of Regional Gross Domestic Product, Open Unemployment Rate and Inflation on the level of Poverty in Aceh Province - Hovonly Aprista Simbolon (Proceedings of AICS - Social Sciences, 2017)
Research aims to understand the influence of regional domestic product its gross (GDP), the open unemployment rate and inflation on the level of poverty in Aceh Province. The type of data on in this research was secondary data of time series between 2007 and 2014. The data collected from regional gross domestic product (GDP), the open unemployment rate and inflation as the independent variable and the number of poor people as dependent variable. The analysis method used in this study is multiple regression analysis, t-test, f-test and the coefficient of determination. The results of the partial showed that GDP, open unemployment rate and inflation influential not significant on poverty level in Aceh Province. Increase regional gross domestic product, the lower the unemployment rate and the rate of inflation will reduce the number of poor people in Aceh Province. A conclusion that in extract from the study is the extent of poverty in the Province of Aceh in an ostensible manner influenced by GDP, the unemployment rate and the inflation rate. Therefore the Aceh provincial Government needs to optimize in GDP sectors and open employment opportunities for the community.